L’ospedale ecclesiastico: un’economia civile (Stato, Chiese e pluralismo confessionale, 2012)
Il contributo - segnalato dal Prof. Raffaele Coppola, che ne attesta la scientificità ed originalità - è destinato alla pubblicazione nella rivista Il diritto ecclesiasticoSOMMARIO: 1. Premessa: l’attualità del tema – 2. Il Welfare State e le “nuove” protezioni sociali – 3. La laicità alla prova: sussidiarietà e cooperazione – 4. L’ente ecclesiastico ospedale classificato – 5. Libertà religiosa e associazionismo.Abstract :With this essay the Author analyses the way hospitals, managed by religious organizations (from here stems the Italian notion of so-called “ecclesiastical hospitals”), act in respect to the health care system, which in Italy is informed by the principle stated in article 32 of the Constitution: this principle affirms that “the Republic safeguards health as a fundamental right of the individual as a collective interest”. In particular, the Author is able to demonstrate that the integration process concerning the ecclesiastical hospitals can be considered either a result of the principle of “Subsidiarity” (in the horizontal sense of the term) or a product of the important role that, in Italian legal system, has been traditionally recognised to the religious groups, in primis to the Catholic ones. Despite a legal context more and more secularised, in Italy religion still plays a crucial role, especially in fields related to the common wealth. In this manner, with their organizations, religious groups can help the State in affirming and protecting the constitutional “values”, including those values which were stemmed from to secular roots.